THE SENSORY FIELDS OF ODOR AND DISGUST AS RELATIONSHIP WITH THE OTHER: NOTES FOR A READING OF THE SENSITIVE IN PEREGRINACIONES DE UNA PARIA OF FLORA TRISTÁN - Mondoñedo, Marcos (2020)
This text is an analysis of the sensitive and its emotional effects on Peregrinaciones de una paria by Flora Tristán. We analyzed a passage of the story taken as a representative case of the relations that in the text can be established between narrative subjectivity, sensitivity, emotion and significance of the other subordinate who, in this case, is the black slave. For this brief analysis, we use some tools of the sensitive semiotics that are consistent with a feminist reading perspective. This latter is relevant because it takes the emotional dimension to approach in a novel way, among other speeches, the texts written by women in the nineteenth century.